Legal Review of the Return of Evidence to a Good Faith Third Party in a Narcotics Case - Limbong, Wintar; Ramadhan, M. Citra; Isnaini, Isnaini (Journal La Sociale, 2025)
The return of evidence to a third party in good faith in a narcotics crime case is an important and complex legal issue. This study aims to analyze the application of the law to the status of evidence, judges' considerations in decision-making, and obstacles faced in returning evidence at the I-02 Medan Military Court, with a focus on Decision Number 16-K/PM. I-02/AD/II/2023. This research uses a qualitative method with a normative and empirical approach through document analysis, in-depth interviews, and literature reviews. The results of the study show that the application of the law refers to Article 46 of the Criminal Procedure Code and Law Number 35 of 2009 concerning Narcotics, with the main principle of protecting the rights of third parties in good faith. The judge's considerations include proof of legal ownership, the non-involvement of a third party in the crime, and the balance of justice. However, the obstacles faced include a lack of ownership documents, difficulty assessing good intentions, complicated administrative processes, and lack of legal understanding by third parties. The conclusion of this study emphasizes the importance of synergy between the application of fair, efficient, and responsive laws and the protection of individual rights. In addition, improvements are needed in the administrative process and education to the public to increase legal understanding. This research makes theoretical and practical contributions to the development of the criminal justice system in Indonesia, especially in the case of narcotics crimes.